1987
DOI: 10.1159/000167442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Naloxone Administration on Endocrine Abnormalities in Chronic Renal Failure

Abstract: In 72 patients with end-stage renal failure and 70 healthy subjects, the influence of blockade of opioid receptors by naloxone on secretion of prolactin, lutropin (LH), follitropin (FSH), adrenocorticotropin (ACTH), somatotropin (HGH), insulin (IRI), glucagon (IR-G), parathyroid hormone (PTH) and calcitonin (CT) was studied. Administration of naloxone stimulated luliberin-induced LH and FSH secretion quantitatively equally in patients and controls. Blockade of opioid receptors was followed by a less marked sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
1991
1991

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Data shown in this paper suggest that the presence of a functioning kidney transplant does not normalize ele vated basal STH plasma levels which occur in chronic uremic patients [4,9], In addition a kind of immunosup pressive therapy exerts a significant influence on hypo glycemia-induced STH secretion. The response of STH secretion to hypoglycemia was significantly suppressed in patients of the azathioprine group as compared with normals and patients treated with ciclosporin.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Data shown in this paper suggest that the presence of a functioning kidney transplant does not normalize ele vated basal STH plasma levels which occur in chronic uremic patients [4,9], In addition a kind of immunosup pressive therapy exerts a significant influence on hypo glycemia-induced STH secretion. The response of STH secretion to hypoglycemia was significantly suppressed in patients of the azathioprine group as compared with normals and patients treated with ciclosporin.…”
Section: Discussionmentioning
confidence: 90%
“…All hormones were assessed by radioimmunoassay according to Grzeszczak et al [4] and Kokot and Stupnicki [11], and creatinine by the routine picric-acid method. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The responses to stimulation and suppres sion tests in various endocrine systems are markedly affected in uremic patients by a blockade of opioid receptors with naloxone [33] . Furthermore, a decrease in the plasma levels of p-END together with a decrease in the plasma levels of growth hormone and parathyroid hormone have been described in patients on a low-protein diet [27].…”
Section: Other Causesmentioning
confidence: 99%
“…High levels of these polypeptides are indeed known to stimulate the secretion of parathyroid hormone (PTH) [I],growth horm one(G H ) [2.3], pituitary thyroid-stimulating hormone (TSH) [2], gonadotropins (LH. FSH) [4,5], prolactin (PRL) [2] and to cause glucose intolerance [6]. Circulating P-endorphin ((3-EP) is high in CRF and this is the most active of these compounds [7], Some years ago a very low-protein diet supplemented with essential amino acids and ketoanalogues (supple mented diet, SD) was introduced in the treatment of severe C R F [8) and it was found that it can slow down the rate of decline of the residual renal function [8,9], reverse secondary hyperparathyroidism [10,II], improve TSH and Tj levels [12], and restore gonadal testosterone (T) secretion in males [13].…”
Section: Introductionmentioning
confidence: 99%